A Survey on Attitude, Awareness, and Knowledge of Patients Regarding the Use of Dental Implants at a Swiss University Clinic - Adib Al-Haj Husain; Olivia De Cicco; Bernd Stadlinger; Fabienne Andrina Bosshard; Valérie Schmidt; Mutlu Özcan; Silvio Valdec (MDPI AG, 2023)
Even though restoring missing teeth and oral tissue with dental implants is perceived by most patients as a positive experience, patients lack access to evidence-based information about different treatment options. In order to provide more accurate information for public dental education in Switzerland and to compare it worldwide, this descriptive cross-sectional survey-based study assessed pre-operative attitudes, awareness, and knowledge of patients. A total of 160 patients with indication for tooth extraction were selected randomly from clinical routine between August 2022 and February 2023. Statistical analysis was performed including the chi-square test based on a significance level of 0.05. The results confirm that most patients (78%) were aware of implants as a treatment option for replacing missing teeth and consider them a prioritized solution (79%). Their primary sources of information are dentists (59%), the Internet (50%), relatives and friends (40%). The majority of patients (84%) wanted the surgical procedure to be performed by a board-certified clinical specialist expecting high functional and aesthetic outcomes. Low levels of knowledge could be observed regarding postoperative care, functionality, and clinical performance of implants. This survey-based study revealed a positive attitude and an acceptable level of awareness and knowledge regarding the use of dental implants.